Study of Tidal Characteristics in The South and North Coastal of Sumenep Regency, Madura - Luhur Moekti Prayogo; Leni Suspidayanti (JURNAL PERIKANAN DAN KELAUTAN, 2020)
Sumenep is one of Madura's regency, which has many islands with a wealth and diversity of natural resources, especially in its marine and coastal areas. With many islands owned, sea transportation in Sumenep is of great importance in the regency. One of the crucial aspects that must be considered related to this transportation is tidal information. This study aims to determine the tidal characteristics in the South and North Coast of Sumenep Regency using the Least Square method. The tide data used in February and September 2020 were obtained from the Geospatial Information Agency (BIG) with an observation interval of one hour. This time was chosen because it represents monsoons' occurrence in Indonesia in the annual season, namely the dry and rainy seasons. The results of this study indicate that the southern coastal area (Giligenting District) has a mixed tidal type, tends to be semi-diurnal with Formzahl numbers of 0.86 and 1.29 (0.25 <F £ 1.5). In comparison, the North coast (Dasuk District) has a Diurnal tidal type with Formzahl numbers of 3.64 and 4.30 (F > 3.0). The different tides are due to the sampling's location representing different geographical conditions, namely open waters (North Coast) and closed waters (Pesisir Selatan). The elevation parameters obtained still need supporting data such as waves, currents, and bathymetry used by policymakers for safety in using sea transportation.